2017
DOI: 10.1016/j.esxm.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of Dapoxetine Treatment in Patients With Premature Ejaculation: A 2-Year Prospective Observational Study

Abstract: IntroductionAlthough dapoxetine is the only oral pharmacologic agent approved for the treatment of premature ejaculation (PE) and is very effective, the discontinuation rate is high.AimTo assess the discontinuation rate of patients with PE and the reasons for discontinuation in real-world practice.MethodsIn total, 182 consecutive patients were enrolled. Type of PE, self-estimated intravaginal ejaculation latency time, and medical history were evaluated in all patients who also completed the erectile function d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 30 publications
0
28
0
1
Order By: Relevance
“…The present study provided further evidence that behavioral methods can lead to significant reductions in PE, with a majority of the participants in the present study improving in terms of their categorization on a validated scale of PE. While the present first-line treatment of PE is associated with a range of side effects, contributing to making treatment with SSRIs unacceptable to most patients, (Jern et al, 2014;Mondaini et al, 2013;Park et al, 2017), no side effects have been reported by the vibrator-assisted start-stop exercises in the present or previous studies, besides complaints concerning difficulty to find time to complete all recommended exercises (Jern, 2014;Zamar, 2012). As for the practical administration of treatment, taking a pill is simple and quick, whereas start-stop exercises necessitate a considerable investment of time and effort.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The present study provided further evidence that behavioral methods can lead to significant reductions in PE, with a majority of the participants in the present study improving in terms of their categorization on a validated scale of PE. While the present first-line treatment of PE is associated with a range of side effects, contributing to making treatment with SSRIs unacceptable to most patients, (Jern et al, 2014;Mondaini et al, 2013;Park et al, 2017), no side effects have been reported by the vibrator-assisted start-stop exercises in the present or previous studies, besides complaints concerning difficulty to find time to complete all recommended exercises (Jern, 2014;Zamar, 2012). As for the practical administration of treatment, taking a pill is simple and quick, whereas start-stop exercises necessitate a considerable investment of time and effort.…”
Section: Discussionmentioning
confidence: 63%
“…At present, selective serotonin reuptake inhibitors (SSRIs) are considered first-line agents for treatment of PE (McMahon, 2015). However, several studies of the only drug approved for treatment of PE (dapoxetine, an SSRI to be taken on demand) in naturalistic settings have reported high discontinuation rates ranging from 70.6 to 89.6% after 12 months, with common reasons for discontinuation being low efficacy, side effects, cost, and loss of interest in sex (Jern, Johansson, Piha, Westberg, & Santtila, 2014;Mondaini et al, 2013;Park et al, 2017). This indicates that further development of treatment options for PE is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high efficacy of SSRIs and associated low rate of adverse events, the proportions of men who stopped using DPX were 79.1% within 6 months and 90.1% at 2 years 73 . The commonest reasons for discontinuation were the following:…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 92%
“… 112 and Sato et al . 111 , where silodosin was compared with other α1-adrenoceptor antagonists 73 . Ideally, before it is possible to fully assess the efficacy of silodosin, there must be a placebo-controlled trial with a more diverse PE population using the ISSM criteria.…”
Section: Management Options: Novel Agentsmentioning
confidence: 99%
“…[19] Uzun etkili SSRİ'lere göre yan etki profili daha iyi olmasına rağmen, dapoksetin tedavisi alan hastaların fiyat ve etkinlik sorunları nedeniyle tedaviden 3, 6, 12 ve 24 ay sonra ilacı bırakma oranları sırasıyla %61,6, %79,1, %87,3, ve %90,1 bulunmuştur. [20] Yaşam boyu PE'li olgulara göre kazanılmış PE (İVEZ ˃ 2 dakika)'li olgularda ilacı bırakma süresi daha kısa ve oranı daha yüksektir.…”
Section: Kısa Etkili Ssri̇unclassified